“Do I need to reinvent myself?” Stigmatization of sport-related identities of Chinese students - Chen, Jiangxi; Ni, Weiguang (Frontiers in Psychology, 2024)
ObjectivesWhile many studies have shown that student-athletes are a stigmatized group and topics related to them have received increasing attention, few studies have focused on the current situation of Chinese sports students (tiyu sheng) with the same dual identity as student-athletes. Thus, this study aims to understand and recognize the negative perceptions that students with sports identities experience in the Chinese educational and cultural context and the impact of these perceptions on them.MethodsThis qualitative study used an interpretive description methodology to collect data through semi-structured, in-depth interviews conducted by the researcher with 11 sports students, 4 regular students, 3 teachers, and 2 parents. Then, the interview data was analyzed using reflective thematic analysis.ResultsThree themes were eventually extracted: (1) The onset and development of stigma, (2) Stigma factors in the spotlight, and (3) the Response to stigmatization by sports students.ConclusionFindings indicated that sports students are subjected to various stigmas under the negative filters of society. The stigmas suffered by sports students vary across school years and levels, and their perceptions of stigmas may also change over time and in different environments. In addition, being subjected to stereotype threat and self-stigma may have hurt some participants. The study’s results also provide evidence that the Internet plays a vital role in exacerbating the development of stigmatization among sports students, which needs to be determined by further research. These findings will contribute to subsequent research on the de-stigmatization of sports students.